Stress Factors among Dental Postgraduate Residents of Lahore, Pakistan - Fizza Tahir; Aleshba Saba Khan; Hina Zafar Raja; Hira Butt; Maila Habib Piracha; Nauman Rauf Khan (Gandhara University, 2021)
OBJECTIVES: The aim of this study was to identify the stress factors among dental postgraduate residents of Lahore, Pakistan. METHODOLOGY: A cross-sectional study was conducted using non-probability convenient sampling techniques. Total 150 dental postgraduate residents were enrolled in this study. Questionnaire was composed of questions regarding stress factors and the influence of stressors on individuals. The data was analyzed; Chi-square test was used to find the statistical association of level of stress with the demographic factors (gender, marital status, and accommodation), professional characteristics (working hours and practice) and impact on the individuals (mood change, weight change and headache). The level of significance was set at P≤0.05. RESULTS: Total 150 individuals responded with a mean age of 29 years (SD +/-2.96). Male to female ratio was 1:2.5. The most prevalent factors that contributed to stress were post-graduate examination (81%), clinical case presentations (80%), competition for higher performance (61%), inconsistency of feedback by supervisors (59%), research program (55%) and fear of failure to treat patients (53%). More than half of the respondents (69%) suffered from mood swings and (65%) from tension headaches followed by clenching and bruxism in nearly half of the residents (50%), musculoskeletal problems (49%) and weight changes (48%) with p-value<0.05. CONCLUSION: Post-graduate examination, competition for higher performance and increased workload are the most common stressors. There is a need to come up with effective strategies in the postgraduate curriculum to tackle stress.